Progesterone Metabolites Produced by Cytochrome P450 3A Modulate Uterine Contractility in a Murine Model. (December 2015) - Patil, Avinash S.; Swamy, Geeta K.; Murtha, Amy P.; Heine, R. Phillips; Zheng, Xiaomei; Grotegut, Chad A.
Objective: We seek to characterize the effect of progesterone metabolites on spontaneous and oxytocin-induced uterine contractility. Study Design: Spontaneous contractility was studied in mouse uterine horns after treatment with progesterone, 2α-hydroxyprogesterone, 6β-hydroxyprogesterone (6β-OHP), 16α-hydroxyprogesterone (16α-OHP), or 17-hydroxyprogesterone caproate (17-OHPC) at 10 −9 to 10 −6 mol/L. Uterine horns were exposed to progestins (10 −6 mol/L), followed by increasing concentrations of oxytocin (1-100 nmol/L) to study oxytocin-induced contractility. Contraction parameters were compared for each progestin and matched vehicle control using repeated measures 2-way analysis of variance. In vitro metabolism of progesterone by recombinant cytochrome P450 3A (CYP3A) microsomes (3A5, 3A5, and 3A7) identified major metabolites. Results: Oxytocin-induced contractile frequency was decreased by 16α-OHP ( P = .03) and increased by 6β-OHP ( P = .05). Progesterone and 17-OHPC decreased oxytocin-induced contractile force ( P = .02 and P = .04, respectively) and frequency ( P = .02 and P = .03, respectively). Only progesterone decreased spontaneous contractile force ( P = .02). Production of 16α-OHP and 6β-OHP metabolites were confirmed in all CYP3A isoforms tested. Conclusion: Progesterone metabolites produced by maternal or fetal CYP3A enzymes influence uterine contractility.